Leisure-time centres for 6–9 year old children in Iceland; policies, practices and challenges - Pálsdóttir, Kolbrún; Kristjánsdóttir, Steingerður (Verlag Barbara Budrich, 2017)
Leisure-time centres (LTC) for six to nine-year-old children have in the last decades become a part of the basic services provided by municipalities in Iceland. LTC provide care and organized leisure-activities during out-of school hours while parents work or study. A national survey from 2014 showed that 92% of municipalities in Iceland operated LTC as opposed to 75% in 2010 and that around 60% of all six-to-nine-year-old children attend leisure-time centres (Pálsdóttir, 2014). However, participation is much higher for children from grades 1 and 2 and declines dramatically in grades 3 and 4. In this article, the authors introduce policy in Iceland with regard to LTC and discuss challenges that lie ahead. (DIPF/Orig.)